Association Between Prescription Drug Insurance and Health Care Utilization Among Medicare Beneficiaries. (April 2018) - Alexander, G. Caleb; Schiman, Cuiping; Kaestner, Robert
Medicare Part D was associated with reduced hospitalizations, yet little is known whether these effects varied across patients and how Part D was associated with length of stay and inpatient expenditures. We used Medicare claims and the Medicare Current Beneficiary Survey from 2002 to 2010 and an instrumental variables approach. Gaining drug insurance through Part D was associated with a statistically significant 8.0% reduction in likelihood of admission across conditions examined. Reductions were generally greater for younger, healthier, and male individuals. Across all conditions, mean length of stay decreased by 3.2% from a baseline of 5.1 days. Part D was associated with a 3.5% reduction in expenditures per admission, reflecting a decrease of $844 from a mean charge of $24, 124 per admission prior to Part D. Thus, Part D was associated with statistically and clinically significant reductions in the probability of admission and length of stay for several common conditions.